CONSISTENT HUMORAL IMMUNITY CONDITION IN PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS ON THE BACKGROUND OF PARASITIC INVASION - Saval’eva, Natal’ya; Shnayder, Stanislav (Journal of Education, Health and Sport, 2015)
The article reveals the results of the immunity humoral chain investigation in patients with the chronic generalized periodontitis (CGP), severity level I-II, in combination with parasitosis. The purpose of the investigation is to verify the role and place of humoral immunity in CGP pathology in patients with parasitosis. Materials and methods. Immunologic investigations were conducted among 540 patients with the chronic generalized periodontitis, severity level I-II, on the background of parasitic invasions (gisrdiasis, enterobiasis, toxocarosis) – (principle groups). The experimental group consisted of 90 CGP patients, severity level I-II, without parasitic invasions. The control group consisted of 30 people without the parodontium pathology and the chronic pathology of other organs and systems, who were considered practically healthy during the investigation. Humoral immunity condition in CGP patients was estimated by the content level of antibodies against etiological inflectional agents in the blood serum and the common antigenic determinant (CAD) of microbes, antimicrobial IgG- antibodies affinity, by the content of IgА. IgМ, IgЕ, CIC, complement activity. Results and conclusions. It is noted that increasing of IgE, CIC and complement levels in blood are the peculiarity of immune structures in the organism of CGP patients with parasitosis, compared with CGP patients without parasitosis. While investigating the qualitative characteristics of the produced antimicrobial antibodies, it was found that in CGP patients, I-II severity level, with parasitosis the antibodies affinity was significantly lower than in CGP patients without parasitosis. Weak antibody immune response to the microbial factor and low produced antimicrobial antibodies affinity, apparently, explain the impossibility for the patient to neutralize and eliminate the bacteria, populating the periodontal pockets, as well as to maintain normal mouth cavity biocenosis. The obtained data also explain, why in CGP patients with parasitosis the degree of microbial colonization of periodontal pockets and species composition of microbial associations is higher than in patients without parasitosis.